(untitled) (Global Journal of Management and Business Research, 2018)
The need for economic theory to address the problem of unsustainable consumption patterns in a developing economy, Nigeria cannot be overemphasized. The literature suggests that present consumption patterns which use up economic resources beyond the capacity of the environment to replenish may make development unsustainable. This study analyzed consumption behavior vis-à-vis the factors that weakly or strongly influence consumption decisions. This key objective of this study is to establish the determinants of consumption among individual households in Agyaragu community of Nasarawa and by inference Nigeria. The study also investigated the extent to which consumption behavior of individuals supported the predictions of conventional models of consumption. A sample of 500 households was drawn from the community population of 22,750, with a response rate of 97%. The model employed alongside others is the Autoregressive Distributed Lagged (ADL) model. The results and findings revealed that individuals do not behave according to the baseline models of consumption. Consumption patterns favored non-durable consumption and necessities. The study recommended the model used in this study as a model of consumption that should incorporate the additional factors revealed by this study. The study, therefore, called for an economic policy and programme that will switch consumption away from non-durables to durables. This recommendation would enhance wealth creation, savings, investment and economic growth and development.